Reduced white matter maturation in the central auditory system of children living with HIV - Madzime, Joanah; Jankiewicz, Marcin; Meintjes, Ernesta M.; Torre, Peter; Laughton, Barbara; van der Kouwe, Andre J. W.; Holmes, Martha (Frontiers in Neuroimaging, 2024)
School-aged children experience crucial developmental changes in white matter (WM) in adolescence. The human immunodeficiency virus (HIV) affects neurodevelopment. Children living with perinatally acquired HIV (CPHIV) demonstrate hearing and neurocognitive impairments when compared to their uninfected peers (CHUU), but investigations into the central auditory system (CAS) WM integrity are lacking. The integration of the CAS and other brain areas is facilitated by WM fibres whose integrity may be affected in the presence of HIV, contributing to neurocognitive impairments. We used diffusion tensor imaging (DTI) tractography to map the microstructural integrity of WM between CAS regions, including the lateral lemniscus and acoustic radiations, as well as between CAS regions and non-auditory regions of 11-year-old CPHIV. We further employed a DTI-based graph theoretical framework to investigate the nodal strength and efficiency of the CAS and other brain regions in the structural brain network of the same population. Finally we investigated associations between WM microstructural integrity outcomes and neurocognitive outcomes related to auditory and language processing. We hypothesized that compared to CHUU the CPHIV group would have lower microstructural in the CAS and related regions. Our analyses showed higher mean diffusivity (MD), a marker of axonal maturation, in the lateral lemniscus and acoustic radiations as well as WM between the CAS and non-auditory regions predominantly in fronto-temporal areas. Most affected WM connections also showed higher axial and radial diffusivity (AD; RD). There were no differences in the nodal properties of the CAS regions between groups. The MD of fronto-temporal and subcortical WM connected CAS regions, including the ILF, IFOF and internal capsule showed negative associations with Sequential processing in the CPHIV group but not in CHUU. The current results point to reduced axonal maturation in WM, marked by higher MD, AD and RD, within and from the CAS. Further, alterations in WM integrity were associated with Sequential processing, a neurocognitive marker of auditory working memory. Our results provide insight into the microstructural integrity of the CAS and related WM in the presence of HIV and link these alterations to auditory working memory.